Survey of Japanese Orphan Drug Program: Factors Related to Successful Marketing Approval - Harada, Kenji (J Clin Pharmacol, 2019)
The basic components of regulatory and supporting policies for orphan drug development appear similar between the United States and Japan, but drugs designated as orphan drugs have been different between the 2 countries. The probabilities of development success (ie, marketing approval) in designated orphan drugs have also been significantly different. In this study, we analyzed recent outcomes of development for orphan drugs designated from 1993 to 2017 in Japan, considering their development and approval status in the United States. Our analysis showed that success for orphan drug development in Japan was apparently associated with prior approval status in the United States. Company size, orphan development experience, and patient enrichment were also positively associated with successful marketing approval. Although similar designations and priority review systems for orphan drugs have been enacted, economic incentives and regulatory conditions provided by the systems seem to be different between the 2 countries, which may lead to varied performance in orphan designation and approval. We need to pay close attention to the impact of industrial global development strategies when comparing the outcomes and performance of different orphan drug promotion systems.